2003
DOI: 10.1089/107999003772084842
|View full text |Cite
|
Sign up to set email alerts
|

Association of Endogenous G-CSF with Anti-Inflammatory Mediators in Patients with Acute Respiratory Distress Syndrome

Abstract: Upregulation of the anti-inflammatory mediators, soluble tumor necrosis factor-alpha receptors I and II (sTNFRI/RII) and interleukin-1 receptor antagonist (IL-1RA), by granulocyte colony-stimulating factor (G-CSF) may contribute to the pathophysiology of lung injury. We determined the relation of endogenous G-CSF to proinflammatory and anti-inflammatory mediators in bronchoalveolar lavage fluid (BALF) and serum of patients with acute respiratory distress syndrome (ARDS) and acute lung injury (ALI). Nineteen pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
(41 reference statements)
1
26
1
Order By: Relevance
“…We also found enhanced levels of GCSF, which is important for neutrophil accumulation and activation in the lungs (43). High levels of GCSF correlate with ARDS in humans (44)(45)(46), and administration of GCSF induces ALI in animals (43,47). We also found elevated levels of IL-6 in the lungs of Nrf2 2/2 mice compared with Nrf2 1/1 mice in response to MV, suggesting that this cytokine may play a role in causing VILI.…”
Section: Discussionmentioning
confidence: 62%
“…We also found enhanced levels of GCSF, which is important for neutrophil accumulation and activation in the lungs (43). High levels of GCSF correlate with ARDS in humans (44)(45)(46), and administration of GCSF induces ALI in animals (43,47). We also found elevated levels of IL-6 in the lungs of Nrf2 2/2 mice compared with Nrf2 1/1 mice in response to MV, suggesting that this cytokine may play a role in causing VILI.…”
Section: Discussionmentioning
confidence: 62%
“…27,28 G-CSF upregulates the production of cytokines that increase alveolar permeability or neutrophil influx, such as tumor necrosis factor (TNF) a, interleukin (IL) 1b, and IL-8. 29,30 In vitro studies also found enhanced secretion of proinflammatory cytokines by isolated alveolar macrophages obtained during neutropenia recovery from rats that received G-CSF, compared with rats that did not receive G-CSF, providing a possible explanation for lung injury exacerbation during G-CSF-induced neutropenia recovery. 18 Our study has some limitations, however.…”
Section: Discussionmentioning
confidence: 96%
“…The role of IL-1Ra in lung injury is not well characterized, although a murine knockout study showed that IL-1Ra may have an antiinflammatory effect in, and promote resolution after, LPS-induced injury (36). Increased BAL IL-1Ra has been shown in patients with ARDS, and is proposed as a potential endogenous antiinflammatory mediator to limit damage in acute lung injury (ALI) (37). Mesenchymal stem cells, which reduce lung injury in animal models, are associated with increased pulmonary IL-1Ra concentrations (38), whereas aerosolized Anankinra, recombinant human IL-1Ra, reduced pulmonary arterial pressure and gene expression of IL-8 and IL-1b in a porcine model of lung injury, suggesting a reparative role for exogenous IL-1Ra (39).…”
Section: Discussionmentioning
confidence: 99%